Boundary layer flow and heat transfer of carbon nanotubes over a moving surface in presence of hydromagnetic - Ahmad Sidin, Aina Anisah; Bachok, Norfifah (Penerbit Universiti Kebangsaan Malaysia, 2024)
The aim of this study is to investigate and analyze the influence of hydromagnetic forces on the boundary layer flow and heat transfer of carbon nanotubes over a moving surface. Both types of carbon nanotubes such as single-wall carbon nanotubes and multi-wall carbon nanotubes are considered in this research with two types of base fluid, namely water and kerosene. The governing nonlinear partial differential equations are transformed into a nonlinear ordinary differential equations by using similarity transformations then solved numerically by implementing bvp4c package in MATLAB software. The results obtained were represented in table and graphically illustrated with different values of the moving parameter, magnetic parameter, and carbon nanotubes volume fraction parameter. Additionally, the graphs included in this research are skin friction coefficients and local Nusselt number besides the velocity profile and temperature profile. The results proved that duality solutions exist when the plate and the free stream move in opposite directions. Moreover, the availability of magnetic parameter causes the boundary layer thickness to become thinner and increase the heat transfer.